Predicting Psychological Well-Being Based on Digital Self-Efficacy and Emotional Intelligence in Students - Zavari, Nasrin; Mahmoudi Mozaffar, Majid (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to investigate the prediction of psychological well-being based on digital self-efficacy and emotional intelligence among students at the Islamic Azad University, South Tehran Branch.Methods and Materials:  The study type is correlational-descriptive and cross-sectional. The statistical population includes all students of the Islamic Azad University, South Tehran Branch, in the academic year 2023-2024. Sampling was conducted using the convenience method, and 200 individuals were selected based on the Morgan table, considering the possibility of statistical attrition. Data collection tools included standardized questionnaires on psychological well-being, digital self-efficacy, and emotional intelligence. Data were analyzed using Pearson correlation and multiple regression methods.Findings:  Results showed that all components of digital self-efficacy and emotional intelligence have a significant relationship with psychological well-being. The highest correlation coefficient was related to the security component in digital self-efficacy (p